Random Forest Optimization Using Particle Swarm Optimization for Diabetes Classification - Pratama, Pangeran Fadillah; Rahmadani, Desvita; Nahampun, Rahma Sani; Harmutika, Della; Rahmadeyan, Akhas; Evizal, Muhammad Fikri (Institute of Research and Publication Indonesia (IRPI)., 2023)
Diabetes mellitus is a chronic degenerative disease caused by a lack of insulin production in the pancreas or the body's ability to use insulin less effectively. According to a report by the World Health Organization (WHO), 4% of the total deaths in the world are caused by diabetes. The International Diabetes Federation (IDF) notes that in 2013 there has been an increase in diabetes sufferers. Indonesia is the seventh place with the largest number of cases of diabetes mellitus. In this study, the method used to classify diabetes is using a random forest algorithm with Particle Swarm Optimization (PSO) optimization. This study resulted in an accuracy of the random forest classification algorithm of 78.2% and 82.1 using PSO optimization with an increase in value of 3.9%. It can be concluded that PSO optimization can provide a better increase in classification accuracy values when compared to the random forest algorithm without PSO optimization